Pirate cinema - Doctorow, Cory (Tor Teen, 2012)
In a dystopian, near-future Britain, sixteen-year-old Trent, obsessed with making movies on his computer, joins a group of artists and activists who are trying to fight a new bill that will criminalize even more harmless internet creativity.